Students' Written Academic Competence and Difficulties in Writing Research Article for Publication - Dian Agustina Purwanto Wakerkwa; Diah Kristina; Dewi Rochsantiningsih (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Publishing research article into a journal has recently been an obligation for many academicians around the globe. This demanding task require proper competence of written academic discourse. This study explored the difficulties faced by the students in the process of writing and submitting their articles into journals and how their competence of academic discourse played a role in this process. The data were gathered through the questionnaire and interview of ten Indonesian master students who were selected based on their writing and submitting research paper experience. Being a qualitative study, the findings of this study are presented and discussed narratively. The findings revealed a positive view of the students’ basic competence of the written academic discourse for publication. Four difficulties were investigated as being experienced by the majority of the participants. Pedagogical implications are offered for the students for their future research publication.